METHODOLOGICAL APPROACHES TO CLASTER POLICY FORMATION IN AGRARIAN FIELD - Ulyanchenko Y.O. (Pressing Problems of Public Administration, 2015)
In article researched the methodological approaches to the formation of cluster policy inthe agrarian sphere. Defined the essence of agricultural clusters, their function and determinedthe possibility of implementation of cluster policy in the agrarian sphere.